2016
DOI: 10.1007/s12471-016-0918-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter closure of paravalvular leaks: state of the art

Abstract: Paravalvular leak (PVL) is a serious complication after surgical valve replacement or after transcatheter aortic valve replacement. Approximately 1–5% of PVLs can lead to serious clinical consequences, including congestive heart failure and/or haemolytic anaemia. For years, surgical re-intervention has been considered the treatment of choice for symptomatic patients with PVLs. However, surgical re-intervention is associated with a high risk of morbidity and mortality. Transcatheter PVL (TPVL) closure is a less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 31 publications
0
54
0
1
Order By: Relevance
“…Additionally, the sheaths and device delivery catheter sizes are smaller than those of ADOs (4–7 Fr) [ 16 ], which facilitates the passage of low-profile catheters from the defect without using an AV loop. The feasibility and safety of using AVP III devices have been reported in the literature [ 2 , 16 18 ]. In our case series, we mostly used AVP III devices, and 16 devices were advanced through 6-Fr or 7-Fr delivery catheters and deployed successfully.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the sheaths and device delivery catheter sizes are smaller than those of ADOs (4–7 Fr) [ 16 ], which facilitates the passage of low-profile catheters from the defect without using an AV loop. The feasibility and safety of using AVP III devices have been reported in the literature [ 2 , 16 18 ]. In our case series, we mostly used AVP III devices, and 16 devices were advanced through 6-Fr or 7-Fr delivery catheters and deployed successfully.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the success rate was satisfactory (86%). In the literature, the technical and clinical success rates ranged from 77% to 86% and 67% to 77%, respectively, and the complication rates were low [ 2 ]. In addition to other studies and registries, our series has shown that TPVLC is a safe and feasible technique and can be used without constructing an AV loop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients with a small PVL remain asymptomatic or present with mild hemolytic anemia and a benign course. Large PVLs are seen in less than 1% of surgeries and can result in heart failure, severe hemolytic anemia, or endocarditis (54,56,57).…”
Section: Structural Abnormalitiesmentioning
confidence: 99%
“…However, with 3D TEE, what used to be serious invasive procedures with significant morbidity and mortality rates are now noninvasive and routine with outcomes comparable to their invasive counterparts. 4,5 As percutaneous procedures quickly become the procedure of choice for many patients, it subsequently has become integral that cardiac anesthesiologists master the techniques associated with 3D TEE.…”
mentioning
confidence: 99%